2008
DOI: 10.1177/0269881108096506
|View full text |Cite
|
Sign up to set email alerts
|

Effects of quetiapine, risperidone, 9-hydroxyrisperidone and ziprasidone on the survival of human neuronal and immune cells in vitro

Abstract: Because there are reports on cytotoxic and cytoprotective effects of antipsychotics, the aim of the present study was to evaluate the impacts of different concentrations (1.6-50 microg/mL) of atypical antipsychotics on the survival of human neuronal (neuroblastoma SH-SY5Y) and immune (monocytic U-937) cells and on energy metabolism (ATP level after the incubation with antipsychotics in the concentration of 25 microg/mL). Statistical analysis showed that incubation for 24 h with the antipsychotics quetiapine, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 36 publications
(46 reference statements)
2
12
0
1
Order By: Relevance
“…Overall, paliperidone had the best at concentrations of 10 and 50 μM, even though it retained a mild cytotoxicity when the high dosage was used. This finding is partly consistent with a recent report from Schmidt et al (2010) in which they also showed that incubation for 24 h with risperidone and paliperidone (9-hydroxy risperidone) led to a significantly enhanced cell survival in SH-SY5Y cells in the lower concentrations. Higher concentrations exerted in part cytotoxic effects, with the exception of quetiapine (Schmidt et al 2010).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Overall, paliperidone had the best at concentrations of 10 and 50 μM, even though it retained a mild cytotoxicity when the high dosage was used. This finding is partly consistent with a recent report from Schmidt et al (2010) in which they also showed that incubation for 24 h with risperidone and paliperidone (9-hydroxy risperidone) led to a significantly enhanced cell survival in SH-SY5Y cells in the lower concentrations. Higher concentrations exerted in part cytotoxic effects, with the exception of quetiapine (Schmidt et al 2010).…”
Section: Discussionsupporting
confidence: 92%
“…This finding is partly consistent with a recent report from Schmidt et al (2010) in which they also showed that incubation for 24 h with risperidone and paliperidone (9-hydroxy risperidone) led to a significantly enhanced cell survival in SH-SY5Y cells in the lower concentrations. Higher concentrations exerted in part cytotoxic effects, with the exception of quetiapine (Schmidt et al 2010). Measurement of ATP contents in SH-SY5Y cell line showed significantly increased levels after a 24-h treatment with 25 μM risperidone and paliperidone (9-hydroxy risperidone), which may represent a high effectiveness in excitement of ATP-dependent cellular activities by these two drugs.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The drug concentrations tested here comprised of haloperidol (20 μM=7.55 μg/ mL; 30 μM=11.27 μg/mL and 40 μM=15 μg/mL) and risperidone (20 μM=8.20 μg/mL; 30 μM=12.31 μg/mL and 40 μM=16.4 μg/mL). These concentrations were chosen in line with the investigation performed by Schmidt et al (2010), whereby the authors evaluated the effect of some antipsychotics, including risperidone, on the survival of human neuronal and immune cells. In the SH-SY5Y and U-937 cells, these concentrations were not cytotoxic.…”
Section: Cell Culture and Treatmentsmentioning
confidence: 99%
“…Both cell lines are considered to be involved in the pathogenesis of schizophrenia. In this model, low concentrations of risperidone (1.6-12.5 μg/mL) increase cell survival, while paliperidone significantly improves survival of SH-SY5Y cells and U-937 cells at a concentration of 1.6 μg/mL [128].…”
Section: Differential Profile Of Paliperidone: Neurotoxicity and Neurmentioning
confidence: 94%